2022
DOI: 10.3322/caac.21753
|View full text |Cite
|
Sign up to set email alerts
|

Clinician communication strategies associated with increased uptake of the human papillomavirus (HPV) vaccine: A systematic review

Abstract: Human papillomavirus (HPV) is currently linked to almost 35,000 new cases of cancer in women and men each year in the United States. Gardasil‐9 (Merck & Company), the only HPV vaccine now available in the United States, is nearly 100% effective at preventing precancers caused by oncogenic HPV types. In the United States, however, only about one half of adolescents are up to date with HPV vaccination. It is well known that health care clinicians’ recommendations play a significant role in parents’ decisions reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
(140 reference statements)
0
15
0
Order By: Relevance
“…However, it should be noted that health care providers have a key role in making their clients aware about HPV vaccination. Research in the US has shown that a strong and presumptive provider recommendation increases HPV vaccine acceptance and uptake significantly [ 20 ] and more and better communication training for health care personnel in Germany could be proposed at least to a similar extent as public awareness campaigns. (2) Vaccine confidence, hesitancy, and safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that health care providers have a key role in making their clients aware about HPV vaccination. Research in the US has shown that a strong and presumptive provider recommendation increases HPV vaccine acceptance and uptake significantly [ 20 ] and more and better communication training for health care personnel in Germany could be proposed at least to a similar extent as public awareness campaigns. (2) Vaccine confidence, hesitancy, and safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Strong provider recommendation has overwhelmingly been demonstrated as the most important factor associated with HPV vaccination acceptance in the literature. 28 , 36–38 Yet, a systematic review of studies published between 2012 and 2019 identified age, geographic, socioeconomic, and racial disparities in HPV vaccination recommendation, with fewer recommendations for patients who were younger, living in the South, nonwhite, low-income, or uninsured. 27 Prior national surveys indicated increasing rates of provider recommendation among 11–12-y-olds from 35% in 2009 to 40% in 2011 39 to 59% in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…43 Other studies have noted associations between receipt of influenza and HPV vaccines, 44 which may indicate that parents who accept HPV vaccination may also have more positive attitudes toward other vaccines that are recommended but not mandatory. Alternatively, substantial research has documented the importance of healthcare provider recommendation in vaccine uptake, 45–47 and it is possible that parents who accept influenza, meningitis, and HPV vaccines are receiving higher quality recommendations. 48 …”
Section: Discussionmentioning
confidence: 99%